STRATEGI PENGEMBANGAN TANAMAN OBAT KELUARGA (TOGA) DI DUSUN KIRINGAN DESA CANDEN KABUPATEN BANTUL - Baqin, Nur; Dewi, Nur Saudah Al Arifa (Agros Journal of Agriculture Science, 2024)
This research aims to determine the internal and external factors that influence the cultivation of family medicinal plants and to design appropriate strategies for cultivating family medicinal plants (TOGA). Research activities were carried out in Kiringan Hamlet, Canden Village, Bantul Regency. This research uses descriptive research with SWOT analysis. The results of the analysis of internal factors that influence the development of family medicinal plants (TOGA) in Kiringan hamlet can be concluded that medicinal plant seeds are easy to obtain, do not require large areas of land, and are recognized as typical products (jamu). Lack of knowledge regarding large-scale utilization, lack of facilities and technology to support production, marketing is still small scale. External factors are the lack of public knowledge of the benefits of toga, and the lack of production facilities and infrastructure resulting in marketing only at a regional scale. Government and non-government support has a big influence on the consumption of medicinal plant products. The strategy to develop medicinal plant cultivation is to provide outreach to the community about the benefits of TOGA and collaborate with the government to open employment opportunities for the community by making more attractive products.